THEORETICAL ANALYSIS OF THE MANAGEMENT OF THE PROCESSES OF ORGANIZING AND CONDUCTING CONTINUOUS PROFESSIONAL PRACTICE OF STUDENTS - Akbarov Behzodbek Saybjon ugli (Western European Studies, 2024)
Continuing professional practice is an important component of higher education and provides students with practical experience and practical skills necessary for their future careers. Effective management of the processes associated with the organization and delivery of continuing professional practice is essential to ensure that students receive a valuable learning experience. This article focuses on the theoretical analysis of management strategies and principles that help to successfully implement continuous professional practice for students of higher education
Keywords: continuous professional practice; theoretical analysis; professional practice